Overlapping of sturge weber syndrome and klippel trenaunay weber syndrome - Rahman, MM; Rahman, SA; Rahman, M; Akhter, S; Kawser, CA (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jan;17(1):78-81. The abstract of this article is available on the PubMed website